A high-strength high-temperature resistant alloy fastener and preparation method thereof

By preparing Ce-Y-Nb-Mo-Fe intermediate alloy in the fastener and using multi-component ceramic alloy cladding to form a thick cladding layer, the problem of insufficient performance of existing fasteners in harsh environments is solved, and high strength, high temperature and wear resistance are achieved.

CN118166258BActive Publication Date: 2025-03-11WUXI STANDARD PARTS FACTORY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410214022.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2025-03-11
Estimated Expiration
2044-02-27

AI Technical Summary

Technical Problem

Existing fastener materials are difficult to meet the needs of high strength, high temperature, wear and corrosion resistance in harsh environments.

Method used

By preparing Ce-Y-Nb-Mo-Fe intermediate alloy and adding it to the fastener matrix, laser cladding treatment was carried out in combination with the multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 400-800 μm.

Benefits of technology

It significantly improves the strength, high temperature resistance, surface hardness and wear resistance of fasteners, and solves the problems of loss and uneven dispersion of rare earth elements during the smelting process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118166258B_ABST
    Figure CN118166258B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength high-temperature resistant alloy fastener and a preparation method thereof, the method comprising the following steps: S1, preparing Ce-Y-Nb-Mo-Fe master alloy; S2, weighing raw materials: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, smelting to obtain molten steel; S3, forging the molten steel ingot into a mold, and rough machining to obtain a fastener blank; S4, heat treatment; S5, using multi-component ceramic alloy cladding powder to perform laser cladding treatment on the heat-treated fastener blank, and fine machining to obtain a high-strength high-temperature resistant alloy fastener. The present invention can effectively improve the strength and heat resistance of the fastener by optimizing and adjusting the composition and adding elements such as Ce, Y, Nb, Mo, Cr, and Ni; and can effectively solve the problems of easy loss of rare earth elements Ce and Y during smelting and difficulty in uniform dispersion of trace element Nb.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fastener materials, and in particular to a high-strength and high-temperature-resistant alloy fastener and a preparation method thereof. Background Art

[0002] Fasteners play the role of connection, positioning and sealing in mechanical components. With the continuous enlargement of various types of machinery, equipment, and construction projects, as well as the continuous increase in power and speed and the continuous change in the application environment, the working conditions of fastener parts have become more severe, so the requirements for fasteners are increasing day by day.

[0003] Stainless steel fasteners have good overall performance and are one of the most widely used fastener materials. However, in some special scenarios with harsh application environments or strict requirements, such as aviation equipment, flight equipment, engines, and navigation equipment, there are higher requirements for fasteners' wear resistance, high temperature resistance, strength, and corrosion resistance, and conventional stainless steel fasteners often cannot meet the requirements.

[0004] By optimizing the composition and improving the process, the corrosion resistance and strength of stainless steel fasteners can be improved. For example, the patent CN102260830B discloses a processing method and heat treatment process for high-strength fasteners. By adjusting the material matching and preparation process, the strength and toughness of steel-based fasteners can be improved, but the wear resistance and high temperature resistance are not reliably improved. Elements such as rare earths can effectively improve the comprehensive performance of steel materials. For example, the patent CN116497288B discloses a rare earth composite weathering steel fastener and its preparation method. However, since the density of rare earths is usually lower than that of molten steel, it is easy to float on the surface of slag or be wrapped by slag to cause burning when added to molten steel. In addition, the amount of rare earth added is small, and it is difficult to disperse evenly in molten steel. These problems make it difficult for such elements to exert their reinforcement effect.

[0005] By forming a protective coating on the surface of the fastener, such as a laser cladding layer, the surface properties of the fastener can be effectively improved. For example, patent CN111876634A discloses a powder alloy material for fastener corrosion protection and a method for preparing a laser cladding layer. By forming a nickel-based laser cladding layer, the fastener's resistance to marine corrosion and hydrogen embrittlement can be significantly improved, the fastener's safety can be improved, and its service life can be extended. Patent CN116770038A discloses a method for preparing a high-performance fastener and a fastener, which uses laser cladding to form a cladding layer on the fastener substrate, which can significantly improve the fastener's surface hardness and wear resistance.

[0006] Laser cladding nickel-based coatings can significantly improve the surface strength, corrosion resistance and hardness of alloy materials (Yuan Qinglong, Feng Xudong, Cao Jingjing, et al. Research on microstructure of laser cladding nickel-based alloy coatings [J]. China Laser, 2010 (8): 5. DOI: CNKI: SUN: JJZZ.0.2010-08-038.). In order to further improve its strength, wear resistance and other indicators, ceramic particles can be added to the nickel-based coating. For example, TiC particles can be directly added to the nickel-based powder to form a TiC-reinforced nickel-based cladding layer (Wang Zhidong, Zhang Jiahao, Wang Mingjing, et al. Laser Research on microstructure and wear resistance of nickel-based cladding layer enhanced by TiC photocladding [J]. Mining and Metallurgical Engineering, 2023, 43(1): 137-140.), TiC has a high melting point, superhardness, chemical stability, and high wear resistance. In theory, it can greatly improve the wear resistance and strength of the nickel-based cladding layer. However, due to the differences in surface properties and density between TiC powder and nickel powder, it is difficult to achieve physical uniform mixing of the two. In addition, due to the poor wettability of TiC with the matrix and nickel, ceramic particles such as TiC are often difficult to disperse evenly in the cladding layer, resulting in a large difference between the actual effect and the theory.

[0007] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a high-strength and high-temperature resistant alloy fastener and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-strength and high-temperature resistant alloy fastener, comprising the following steps:

[0010] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0011] Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, vacuumized, and then argon gas is introduced to 0.05-0.3MPa, and smelted at 1450-1700°C for 30-90min, cooled to 650-850°C, kept warm for 5-30min, and then cooled to room temperature at a cooling rate of 10-30°C / min to obtain a Ce-Y-Nb-Mo-Fe master alloy;

[0012] The components of the Ce-Y-Nb-Mo-Fe master alloy include, by mass percentage:

[0013] Ce: 1.5-8.1%, Y: 0.9-5.7%, Nb: 0.45-1.26%, Mo: 4.5-18.3%, the balance is Fe and unavoidable impurity elements;

[0014] S2. Weigh raw materials: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, and smelt them to obtain molten steel;

[0015] S3, forging the molten steel ingot into a shape, and rough-processing to obtain a fastener blank;

[0016] S4, heat treatment;

[0017] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0018] Preferably, the fastener blank comprises, by mass percentage:

[0019] C: 0.27-0.42%, Si: 0.15-0.36%, Mn: 0.53-0.82%, Cr: 1.77-3.92%, Ni: 4.75-8.93%, Mo: 0.22-0.69%, V: 0.20-0.45%, Ce: 0.096-0.288%, Y: 0.066-0.198%, Nb: 0.017-0.051%, and the balance is Fe and unavoidable impurity elements.

[0020] Preferably, the method for preparing the high-strength and high-temperature resistant alloy fastener comprises the following steps:

[0021] S1. preparing Ce-Y-Nb-Mo-Fe master alloy;

[0022] Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, vacuumized, and then argon gas is introduced to 0.05-0.3MPa, and smelted at 1450-1700°C for 30-90min, cooled to 650-850°C, kept warm for 5-30min, and then cooled to room temperature at a cooling rate of 10-30°C / min to obtain a Ce-Y-Nb-Mo-Fe master alloy;

[0023] The components of the Ce-Y-Nb-Mo-Fe master alloy include the following by mass percentage:

[0024] Ce: 1.5-8.1%, Y: 0.9-5.7%, Nb: 0.45-1.26%, Mo: 4.5-18.3%, the balance is Fe and unavoidable impurity elements;

[0025] S2. Weigh raw materials: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add into electric melting furnace, smelt at 1500-1620° C. for 30-60 min, perform LF refining outside the furnace, the refining temperature is 1630-1680° C., the refining time is 5-30 min, and perform VD vacuum degassing to obtain molten steel;

[0026] S3, casting the molten steel, forging the obtained ingot at 1000-1150°C, final forging at 900-950°C, air cooling to 300-350°C after forging and keeping the temperature for 4-10h to obtain a fastener blank;

[0027] S4. Heat treatment: keep the fastener blank at 750-900℃ for 1-4h, cool to 500-600℃, keep for 4-10h, and then oil cool to room temperature;

[0028] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 400-800 μm on the surface of the fastener blank, and then fine-processed to obtain a high-strength and high-temperature resistant alloy fastener.

[0029] Preferably, step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at a cooling rate of 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

[0030] Preferably, the composition of the Ce-Y-Nb-Mo-Fe master alloy includes the following by mass percentage:

[0031] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0032] During the smelting process of step S2, the addition amount of the Ce-Y-Nb-Mo-Fe master alloy is 2-6% of the total raw material mass.

[0033] Preferably, the fastener blank comprises, by mass percentage:

[0034] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.57%, Ce: 0.24%, Y: 0.165%, Nb: 0.0425%, and the remainder is Fe and inevitable impurity elements.

[0035] Preferably, the multi-element ceramic alloy cladding powder is prepared by the following method:

[0036] S5-1. Preparation of gC 3 N 4 ;

[0037] S5-2, gC 3 N 4 , butyl titanate, and ferric acetate were used as raw materials to prepare composite oxide powder gC by mixing and calcining 3 N 4 -TiFeO;

[0038] S5-3, through the thermal reduction method, using the composite oxide powder gC 3 N 4 -TiFeO preparation of ceramic alloy composite Ti(C,N)@Fe:

[0039] S5-4, coating the surface of Ti(C,N)@Fe with a NiWCoB multi-element alloy layer by chemical plating to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe;

[0040] S5-5. Evenly mix the multi-component ceramic alloy powder and the nickel powder to obtain the multi-component ceramic alloy cladding powder.

[0041] Preferably, the multi-element ceramic alloy cladding powder is prepared by the following method:

[0042] S5-1. Place urea in a muffle furnace, heat to 580-700°C at 5-10°C / min, and calcine for 2-6h to obtain gC 3 N 4 ;

[0043] S5-2, take 1.25-3.23g gC 3 N 4 , 0.0155-0.07 mol butyl titanate, 0.113-0.45 mol ferric acetate, mixed and ground for 45-90 min, the resulting mixture was calcined at 550-680 ° C for 1-4 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder gC 3 N 4 -TiFeO;

[0044] S5-3, the composite oxide powder gC 3 N 4 -TiFeO is added into a tubular vacuum furnace, reacted at 920-1100°C for 1-5h in a hydrogen atmosphere, cooled to room temperature, and ground into powder to obtain a ceramic alloy composite Ti(C,N)@Fe;

[0045] S5-4. A NiWCoB multi-element alloy layer is coated on the surface of Ti(C,N)@Fe by chemical plating process to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe:

[0046] S5-4-1, washing the ceramic alloy composite Ti(C,N)@Fe prepared in step S5-3 with a hydrochloric acid solution having a mass fraction of 2-10%, then washing with deionized water until neutral, then washing with ethanol, and drying;

[0047] S5-4-2, adding 7-23 g / L SnCl 2 The solution is treated for 5-20 minutes, and then the product is taken out, washed with deionized water, and added to the multi-element plating solution. After stirring for 4-15 minutes, the temperature is raised to 65-77°C, and the pH value of the multi-element plating solution is controlled to be 10-11. The plating is performed for 30-90 minutes. After the end, the product is allowed to stand for 2-10 minutes, and then filtered. The solid product is washed with deionized water, dried, and ground to obtain a multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe;

[0048] The amount of ceramic alloy composite Ti(C,N)@Fe added to each 1L of multi-element plating solution is 8-30g;

[0049] The components of the multi-element plating solution include: 22-40 g / L nickel sulfate, 3-18 g / L sodium tungstate, 5-20 g / L cobalt sulfate, 1-5 g / L sodium tetraborate, 2-10 g / L sodium borohydride, 5-25 g / L sodium citrate, 5-20 g / L ammonium chloride, and 10-30 g / L EDTA;

[0050] S5-5. Mix the multi-component ceramic alloy powder and nickel powder in a mass ratio of 0.5-4.5:10, and ball-mill for 1-5 hours under argon protection to obtain multi-component ceramic alloy cladding powder.

[0051] Preferably, the process parameters of the laser cladding treatment in step S5 are: the heat source for cladding is a fiber laser with a power of 2.5-5.0kW, the focal spot diameter of the laser beam is 1.0-4.5mm, the scanning rate is 3-15mm / s, and a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 30-100g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 5-20L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 10-30L / min.

[0052] The present invention also provides a high-strength and high-temperature-resistant alloy fastener, which is prepared by the method described above.

[0053] The beneficial effects of the present invention are:

[0054] In the first aspect of the present invention, by optimizing and adjusting the composition, elements such as Ce, Y, Nb, Mo, Cr, and Ni are added to the steel, which can effectively improve the strength and heat resistance of the prepared fastener;

[0055] In the second aspect of the present invention, by pre-preparing a Ce-Y-Nb-Mo-Fe master alloy with stable composition, elements such as Ce, Y, Nb, and Mo are introduced into the fastener matrix, which can effectively solve the problems of easy loss of rare earth elements Ce and Y during smelting and difficulty in uniform dispersion of trace element Nb;

[0056] In a third aspect of the present invention, laser cladding treatment is performed on the fastener using self-made multi-component ceramic alloy cladding powder to form a cladding layer on the surface of the fastener, which can significantly improve its surface strength, high temperature hardness and wear resistance;

[0057] In the multi-component ceramic alloy cladding powder of the present invention, the NiWCoB coating changes the surface state of the ceramic particles, increases the wettability between the ceramic particles and the nickel-based powder, enables the ceramic particles to be evenly dispersed in the cladding layer, and reduces the difference in thermal expansion properties between the multi-component ceramic alloy powder and the nickel-based powder, thereby reducing the thermal stress and crack tendency in the cladding layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a flow chart of the method for preparing the high-strength and high-temperature-resistant alloy fastener of the present invention;

[0059] Figure 2 is an XRD spectrum of the cladding layer formed on the surface of the fastener blank in Example 1 of the present invention;

[0060] Figure 3 The surface hardness test results of the present invention at 600°C for different holding times;

[0061] Figure 4 This is the wear resistance test result of the present invention. DETAILED DESCRIPTION

[0062] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0063] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0064] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0065] The present invention provides a high-strength high-temperature resistant alloy fastener, and a preparation method thereof comprises the following steps:

[0066] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0067] Ce powder, Y powder, FeNb60 powder (i.e., Nb mass fraction is 60%), Mo powder, and Fe powder are added into a vacuum induction heating melting furnace, evacuated, and then argon gas is introduced to 0.05-0.3MPa, smelted at 1450-1700°C for 30-90min, cooled to 650-850°C, kept warm for 5-30min, and then cooled to room temperature at a cooling rate of 10-30°C / min to obtain a Ce-Y-Nb-Mo-Fe master alloy;

[0068] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0069] Ce: 1.5-8.1%, Y: 0.9-5.7%, Nb: 0.45-1.26%, Mo: 4.5-18.3%, the balance is Fe and unavoidable impurity elements;

[0070] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1500-1620° C. for 30-60 min, perform LF refining outside the furnace, the refining temperature is 1630-1680° C., the refining time is 5-30 min, and perform VD vacuum degassing to obtain molten steel;

[0071] S3, casting the molten steel, forging the obtained ingot at 1000-1150°C, final forging at 900-950°C, air cooling to 300-350°C after forging and keeping the temperature for 4-10h to obtain a fastener blank;

[0072] The composition of the fastener blank includes, by mass percentage:

[0073] C: 0.27-0.42%, Si: 0.15-0.36%, Mn: 0.53-0.82%, Cr: 1.77-3.92%, Ni: 4.75-8.93%, Mo: 0.22-0.69%, V: 0.20-0.45%, Ce: 0.096-0.288%, Y: 0.066-0.198%, Nb: 0.017-0.051%, and the balance is Fe and unavoidable impurity elements.

[0074] S4. Heat treatment: keep the fastener blank at 750-900℃ for 1-4h, cool to 500-600℃, keep for 4-10h, and then oil cool to room temperature;

[0075] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 400-800 μm on the surface of the fastener blank, and then fine-processed to obtain a high-strength and high-temperature resistant alloy fastener.

[0076] In a preferred embodiment, the composition of the Ce-Y-Nb-Mo-Fe master alloy includes the following by mass percentage:

[0077] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0078] During the smelting process of step S2, the addition amount of Ce-Y-Nb-Mo-Fe master alloy is 2-6% of the total raw material mass.

[0079] In a preferred embodiment, the process parameters of the laser cladding treatment are: the heat source for cladding is a fiber laser with a power of 2.5-5.0kW, the focal spot diameter of the laser beam is 1.0-4.5mm, the scanning rate is 3-15mm / s, and a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 30-100g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 5-20L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 10-30L / min.

[0080] In the present invention, the multi-component ceramic alloy cladding powder is prepared by the following method:

[0081] S5-1. Preparation of gC 3 N 4 : Place urea in a muffle furnace, heat to 580-700℃ at 5-10℃ / min, and calcine for 2-6h to obtain gC 3 N 4 ;

[0082] S5-2, gC 3 N4 , butyl titanate, and ferric acetate were used as raw materials to prepare composite oxide powder gC by mixing and calcining 3 N 4 -TiFeO:

[0083] Take 1.25-3.23g gC 3 N 4 , 0.0155-0.07 mol butyl titanate, 0.113-0.45 mol ferric acetate, mixed and ground for 45-90 min, the resulting mixture was calcined at 550-680 ° C for 1-4 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder gC 3 N 4 -TiFeO;

[0084] S5-3, the composite oxide powder gC 3 N 4 -TiFeO is added into a tubular vacuum furnace, reacted at 920-1100°C for 1-5h in a hydrogen atmosphere, cooled to room temperature, and ground into powder to obtain a ceramic alloy composite Ti(C,N)@Fe;

[0085] S5-4. A NiWCoB multi-element alloy layer is coated on the surface of Ti(C,N)@Fe by chemical plating process to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe:

[0086] S5-4-1, washing the ceramic alloy composite Ti(C,N)@Fe prepared in step S5-3 with a hydrochloric acid solution having a mass fraction of 2-10%, then washing with deionized water until neutral, then washing with ethanol, and drying;

[0087] S5-4-2, adding 7-23 g / L SnCl 2 The solution is treated for 5-20 minutes, and then the product is taken out, washed with deionized water, and added to the multi-element plating solution. After stirring for 4-15 minutes, the temperature is raised to 65-77°C, and the pH value of the multi-element plating solution is controlled to be 10-11. The plating is performed for 30-90 minutes. After the end, the product is allowed to stand for 2-10 minutes, and then filtered. The solid product is washed with deionized water, dried, and ground to obtain a multi-element ceramic alloy powder.

[0088] The amount of ceramic alloy composite Ti(C,N)@Fe added to each 1L of multi-element plating solution is 8-30g;

[0089] The components of the multi-element plating solution include: 22-40 g / L nickel sulfate, 3-18 g / L sodium tungstate, 5-20 g / L cobalt sulfate, 1-5 g / L sodium tetraborate, 2-10 g / L sodium borohydride, 5-25 g / L sodium citrate, 5-20 g / L ammonium chloride, and 10-30 g / L EDTA;

[0090] S5-5. Mix the multi-component ceramic alloy powder and nickel powder as a base powder in a mass ratio of 0.5-4.5:10, and ball-mill for 1-5 hours under argon protection to obtain multi-component ceramic alloy cladding powder.

[0091] The fasteners in the present invention can be various conventional products that play a role in fastening and connecting, such as bolts, studs, screws, screws, nuts, fastening washers, pins, rivets, etc.

[0092] In the first aspect of the present invention, by optimizing and adjusting the composition, adding elements such as Ce, Y, Nb, Mo, Cr, and Ni, the strength and heat resistance of the fastener can be effectively improved;

[0093] Cr can improve the hardness, wear resistance and corrosion resistance of steel; Mo can improve the high temperature resistance of steel and increase the strength and hardness of steel; Ni can improve the heat resistance and corrosion resistance of steel; Ce can refine the grains, improve the stability of grain boundaries, and has strong deoxidation and desulfurization capabilities, can improve the distribution and morphology of inclusions in steel, and can enhance the strength; Y can prevent grain growth, improve strength, oxidation resistance, and improve plasticity; Nb can refine the grains and reduce overheating sensitivity and brittleness, improve strength, and also improve resistance to atmospheric corrosion and resistance to hydrogen, nitrogen, and ammonia corrosion at high temperatures.

[0094] In the second aspect of the present invention, by pre-preparing a Ce-Y-Nb-Mo-Fe intermediate alloy with stable composition and introducing elements such as Ce, Y, Nb, and Mo into the fastener matrix, the problems of easy loss of rare earth elements Ce and Y during smelting and difficulty in uniform dispersion of trace element Nb can be effectively solved.

[0095] The density of Ce and Y is lower than that of molten steel. The density of Ce is 6.77 g / cm 3 、Y density 4.47g / cm 3 、Fe density 7.86g / cm 3, directly added to the molten steel, it is easy to float on the surface of the slag or be wrapped by the slag, resulting in burning. The amount of Ce, Y, and Nb added is small, and there are differences in density and surface properties between them and the molten steel. It is also difficult to disperse them evenly in the molten steel. These problems make it difficult for such trace elements to exert their reinforcing effect. In the present invention, by adding the trace elements Ce, Y, and Nb in the form of a pre-prepared Ce-Y-Nb-Mo-Fe intermediate alloy, on the one hand, the density of the intermediate alloy is closer to that of the molten steel (the density of Mo is 10.2g / cm 3 , which can improve the density of the overall master alloy), can reduce the floating of Ce and Y, and the trace elements Ce, Y, and Nb are wrapped by Fe. After being added to the molten steel, Fe is easily wetted by the molten steel and retained in the molten steel and fully dispersed. The Ce, Y, and Nb wrapped by Fe can thus smoothly enter the molten steel and disperse evenly with the entrainment of Fe, and ultimately the loss of Ce, Y, and Nb can be reduced, and they are fully dispersed in the fastener matrix to effectively play their respective reinforcement roles, thereby significantly improving the strength and heat resistance of the fastener.

[0096] In the third aspect of the present invention, by using self-made multi-component ceramic alloy cladding powder to perform laser cladding treatment on the fastener, a cladding layer is formed on the surface of the fastener, which can significantly improve its surface strength, high temperature hardness and wear resistance. Laser cladding nickel-based coating can improve the surface strength, corrosion resistance, hardness, etc. of alloy materials, but the improvement effect is limited. In the present invention, by introducing ceramic alloys, the enhancement effect on the surface performance of fasteners can be further improved. The following is a detailed description of its main principles to facilitate understanding of the present invention.

[0097] 1. The present invention firstly prepares yellow block gC by the traditional method of calcining urea. 3 N 4 (Ma Yujie, Cui Lifeng. Preparation and adsorption properties of TiN-TiC composites[J]. Nonferrous Metal Materials and Engineering, 2019, 40(4):5. DOI:CNKI:SUN:SHHA.0.2019-04-001.)

[0098] 2. Then through gC 3 N 4 With titanate butyl ester and ferric acetate at high temperature to form titanium and iron oxides and gC 3 N 4 Doped composite oxide powder gC 3 N 4 -TiFeO;

[0099] 3. Then composite oxide powder gC 3 N 4-TiFeO is reduced to form titanium-doped iron core particles under the action of high temperature and reducing gas. 3 N 4 C and N decomposed at high temperature react with titanium to form TiC, TiN and their composite particles, which are evenly coated on the surface of the iron core particles, and finally form a ceramic alloy composite with a core carrier with iron as the main component and the outer layer of Ti(C,N) ceramic alloy particles coated with a core-shell structure: Ti(C,N)@Fe.

[0100] In this process, C and Ti generate TiC phase, N and Ti generate TiN phase, TiC phase and TiN phase belong to isomorphic structure, C atoms in TiC lattice can be replaced by N atoms in any proportion to form continuous solid solution phase Ti(C,N), so the system of the present invention contains TiC, TiN, Ti(C,N) mixed ceramic phase, Ti(C,N) has the advantages of both TiC and TiN, and also has higher oxidation resistance, hardness, wear resistance and heat resistance than them;

[0101] As the main component of the core, Fe can play the following two roles:

[0102] First aspect:

[0103] The ceramic alloy particles Ti(C,N) are loaded by core microspheres with Fe as the main component, which can reduce the agglomeration of the metal-ceramic composite during chemical plating, and are conducive to fully coating the NiWCoB alloy coating on the surface of the ceramic alloy particles;

[0104] Second aspect:

[0105] Ceramic alloy particles, such as TiC and TiN, have a large density difference with Ni and poor wettability, and also have poor wettability with the iron matrix. For example, the wetting angle of TiC to liquid Fe is 41° in a vacuum atmosphere at 1550°C (Huang Boyun. Principles of Powder Metallurgy [M], Beijing: Metallurgical Industry Press, 2002.). The above defects easily lead to the following problems: (1) When the multi-component ceramic alloy powder is mixed with nickel powder as the base powder to prepare the multi-component ceramic alloy cladding powder, the multi-component ceramic alloy powder and the nickel powder are difficult to mix evenly; (2) Due to the poor wettability with Ni, the ceramic alloy particles are difficult to disperse evenly in the nickel-based cladding layer; (3) Due to the poor wettability with Fe, when the high temperature of the laser forms a molten pool at the interface, the ceramic alloy particles are not easy to break through the interface and enter the side of the fastener matrix, and the ceramic alloy phase that plays a reinforcing role near the interface will be reduced, which is not conducive to improving the interface strength.

[0106] In the present invention, the structural system in which Fe is used as the core to load ceramic alloy particles and is combined with the NiWCoB alloy coating can well overcome the above problems. Specifically: First, in the structural system, the introduction of Fe and NiWCoB alloy coating can improve the overall density, which is conducive to its uniform mixing with nickel powder; secondly, when the high temperature of the laser forms a molten pool at the interface, the Fe in the multi-component ceramic alloy cladding powder wets the molten pool of the fastener matrix, and the Fe is entrained and dissolved in the matrix, which can help the ceramic alloy particles enter the interface, thereby forming a pinning effect at the interface between the cladding layer and the matrix, significantly improving the bonding strength between the cladding layer and the matrix; furthermore, the coating of the NiWCoB alloy coating can change the surface properties of the ceramic alloy particles, so that it can be well mixed with the nickel powder, and when the cladding layer is formed at high temperature, the NiWCoB alloy coating can solve the problem of poor wettability between the ceramic alloy particles and nickel, so that it can be evenly dispersed in the nickel-based cladding layer. The NiWCoB alloy coating will be further described below.

[0107] 4. Finally, the present invention coats a NiWCoB alloy coating on the ceramic alloy composite Ti(C,N)@Fe by chemical plating to obtain a core-shell structure system of multi-component ceramic alloy powder NiWCoB@Ti(C,N)@Fe, in which the core is loaded with ceramic alloy particles and the surface of the shell ceramic alloy particles is further coated with a NiWCoB alloy coating;

[0108] Among them, W has good compatibility with ceramic alloy particles. W is coated on ceramic alloy particles in the form of coating components, which can promote W and ceramic alloy particles to exist in the matrix system in a fully and uniformly mixed state, so that the following benefits can be obtained: Ti (C, N) phase is dispersed on the W grain boundary, which plays a role in pinning the grain boundary and increasing the resistance to grain boundary migration, thereby hindering the aggregation and growth of W particles during high temperature, playing a role in refining W grains, and more conducive to the reinforcement of W on the matrix; on the other hand, since W can exist in a uniformly mixed state with ceramic alloy particles, it is more conducive to the formation of WC phase between W and the free state C in the ceramic alloy particles during the high temperature process of laser cladding, and the WC phase can further improve the wear resistance, hardness and thermal strength of the material.

[0109] Among them, Co in the coating composition can provide good anti-oxidation performance and prevent the multi-component ceramic alloy powder from oxidation; Co can also improve the thermal strength and high-temperature hardness of the cladding layer.

[0110] Among them, B helps to improve the uniformity of the Co phase, B can refine the WC grain structure and inhibit grain growth, and B can also form a high-hardness W-Co-B ternary alloy phase with W and Co, which significantly improves the hardness and strength; since boron can form alloy element borides, carborides, oxides, boron nitride, etc., the B introduced in the coating can maintain a uniform mixing state with W, Co, Ti, etc., and make W, Co, and Ti form a competitive advantage over B. WC can preferentially form a W-Co-B ternary alloy phase with B, and free Ti can efficiently form titanium diboride TiB with B. 2 , can improve hardness and high temperature oxidation resistance.

[0111] Among them, Ni, as the main component of the alloy coating layer, can reduce the difference in properties between the multi-component ceramic alloy powder and the nickel-based powder, which is beneficial to its uniform mixing with the nickel-based powder, and by improving the wettability of the multi-component ceramic alloy powder and nickel, it can promote its uniform dispersion in the nickel-based cladding layer. At the same time, nickel can improve the hardness and heat resistance of the cladding layer.

[0112] NiWCoB coating changes the surface state of ceramic particles, increases the wettability between ceramic particles and nickel-based powder, enables ceramic particles to be evenly dispersed in the cladding layer, reduces the difference in thermal expansion properties between multi-component ceramic alloy powder and nickel-based powder, and reduces thermal stress and crack tendency in the cladding layer.

[0113] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0114] The multi-element ceramic alloy cladding powder NiWCoB@Ti(C,N)@Fe involved in the following embodiments is prepared by the following method:

[0115] S5-1. Preparation of gC 3 N 4 : Place urea in a muffle furnace, heat to 650°C at 8°C / min, and calcine for 4h to obtain gC 3 N 4 ;

[0116] S5-2, take 1.66g gC 3 N 4 , 0.035 mol butyl titanate, and 0.150 mol ferric acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder gC 3 N 4 -TiFeO;

[0117] S5-3, the composite oxide powder gC 3 N4 -TiFeO was added into a tubular vacuum furnace, reacted at 1050°C for 3 h in a hydrogen atmosphere, cooled to room temperature, and ground into powder to obtain a ceramic alloy composite Ti(C,N)@Fe;

[0118] S5-4. A NiWCoB multi-element alloy layer is coated on the surface of Ti(C,N)@Fe by chemical plating process to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe:

[0119] S5-4-1, washing the ceramic alloy composite Ti(C,N)@Fe prepared in step S5-3 with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying;

[0120] S5-4-2, adding 16 g / L SnCl 2 The solution is treated for 5-20 minutes, and then the product is taken out, washed with deionized water, and added to the multi-element plating solution. After stirring for 10 minutes, the temperature is raised to 70°C, and the pH value of the multi-element plating solution is controlled to 11 with sodium hydroxide. The plating is performed for 60 minutes. After the end, the product is allowed to stand for 5 minutes, and then filtered. The solid product is washed with deionized water, dried, and ground to obtain a multi-element ceramic alloy powder.

[0121] Among them, the amount of ceramic alloy composite Ti(C,N)@Fe added to each 1L of multi-element plating solution is 22g;

[0122] The components of the multi-element plating solution include: 35 g / L nickel sulfate, 8 g / L sodium tungstate, 12 g / L cobalt sulfate, 2.5 g / L sodium tetraborate, 5 g / L sodium borohydride, 15 g / L sodium citrate, 8 g / L ammonium chloride, and 15 g / L EDTA;

[0123] S5-5. Mix the multi-component ceramic alloy powder and nickel powder as a base powder in a mass ratio of 3:10, and ball-mill for 2 hours under argon protection to obtain multi-component ceramic alloy cladding powder.

[0124] The multi-component ceramic alloy cladding powder includes the following components by weight percentage:

[0125] Ti: 4.45%, Fe: 22.25%, N: 2.26%, C: 1.45%, W: 3.31%, Co: 2.32%, B: 0.66%, and the remainder is Ni and inevitable impurity elements.

[0126] Example 1

[0127] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0128] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0129] Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

[0130] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0131] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0132] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0133] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 2% of the total raw material mass;

[0134] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0135] The composition of the fastener blank includes, by mass percentage:

[0136] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.228%, Ce: 0.096%, Y: 0.066%, Nb: 0.017%, and the remainder is Fe and inevitable impurity elements.

[0137] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0138] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0139] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0140] Reference Figure 2 , is the XRD spectrum of the cladding layer formed on the surface of the fastener blank in Example 1.

[0141] Example 2

[0142] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0143] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0144] Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

[0145] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0146] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0147] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0148] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 3% of the total raw material mass;

[0149] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0150] The composition of the fastener blank includes, by mass percentage:

[0151] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.342%, Ce: 0.144%, Y: 0.099%, Nb: 0.0255%, and the remainder is Fe and inevitable impurity elements.

[0152] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0153] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0154] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0155] Example 3

[0156] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0157] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0158] Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

[0159] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0160] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0161] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0162] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 4% of the total raw material mass;

[0163] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0164] The composition of the fastener blank includes, by mass percentage:

[0165] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.456%, Ce: 0.192%, Y: 0.132%, Nb: 0.034%, and the remainder is Fe and inevitable impurity elements.

[0166] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0167] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0168] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0169] Example 4

[0170] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0171] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0172] Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650° C. for 45 min, cooled to 700° C., kept warm for 20 min, and then cooled to room temperature at 20° C. / min to obtain a Ce-Y-Nb-Mo-Fe master alloy;

[0173] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0174] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0175] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0176] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 5% of the total raw material mass;

[0177] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0178] The composition of the fastener blank includes, by mass percentage:

[0179] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.57%, Ce: 0.24%, Y: 0.165%, Nb: 0.0425%, and the remainder is Fe and inevitable impurity elements.

[0180] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0181] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0182] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0183] Example 5

[0184] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0185] S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy:

[0186] Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

[0187] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0188] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0189] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0190] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 6% of the total raw material mass;

[0191] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0192] The composition of the fastener blank includes, by mass percentage:

[0193] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.684%, Ce: 0.288%, Y: 0.198%, Nb: 0.051%, and the remainder is Fe and inevitable impurity elements.

[0194] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0195] S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, which is then fine-processed to obtain a high-strength, high-temperature-resistant alloy fastener.

[0196] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0197] Comparative Example 1

[0198] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0199] S1. Weigh the raw materials: C, Si, Mn, Cr, Ni, V, Fe according to the weight ratio, add them into an electric melting furnace, smelt at 1600°C for 45min, perform LF refining outside the furnace, the refining temperature is 1650°C, the refining time is 15min, and perform VD vacuum degassing to obtain molten steel;

[0200] S2, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0201] The composition of the fastener blank includes, by mass percentage:

[0202] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, and the remainder is Fe and inevitable impurity elements.

[0203] S3, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0204] S4. Use multi-element ceramic alloy cladding powder to perform laser cladding treatment on the heat-treated fastener blank to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, and then fine-process it to obtain a high-strength and high-temperature resistant alloy fastener; the specific steps are the same as those in Example 4 and will not be repeated here.

[0205] Comparative Example 2

[0206] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0207] S1. Prepare Ce-Y-Nb-Mo-Fe master alloy. The specific steps are the same as those in Example 4 and will not be repeated here;

[0208] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0209] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 5% of the total raw material mass;

[0210] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0211] The composition of the fastener blank includes, by mass percentage:

[0212] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.57%, Ce: 0.24%, Y: 0.165%, Nb: 0.0425%, and the remainder is Fe and inevitable impurity elements.

[0213] S4. Heat treatment: keep the fastener blank at 850°C for 2h, cool it to 600°C, keep it for 7h, then oil cool it to room temperature, and then finish it to obtain a high-strength and high-temperature resistant alloy fastener.

[0214] Comparative Example 3

[0215] A high-strength high-temperature resistant alloy fastener, the preparation method of which comprises the following steps:

[0216] S1. Prepare Ce-Y-Nb-Mo-Fe master alloy. The specific steps are the same as those in Example 4 and will not be repeated here;

[0217] The composition of Ce-Y-Nb-Mo-Fe master alloy includes by mass percentage:

[0218] Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements;

[0219] S2. Weigh the raw materials according to the weight ratio: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add them into an electric melting furnace, smelt at 1600° C. for 45 min, perform LF refining outside the furnace at a refining temperature of 1650° C. for 15 min, and perform VD vacuum degassing to obtain molten steel;

[0220] The addition amount of Ce-Y-Nb-Mo-Fe master alloy is 5% of the total raw material mass;

[0221] S3, casting the molten steel, forging the obtained ingot at 1100°C, final forging at 900°C, air cooling to 350°C and keeping the temperature for 6 hours after forging, to obtain a fastener blank;

[0222] The composition of the fastener blank includes, by mass percentage:

[0223] C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.57%, Ce: 0.24%, Y: 0.165%, Nb: 0.0425%, and the remainder is Fe and inevitable impurity elements.

[0224] S4, heat treatment: keep the fastener blank at 850℃ for 2h, cool to 600℃, keep for 7h, and then oil cool to room temperature;

[0225] S5. The fastener blank after heat treatment is subjected to laser cladding treatment using nickel powder to form a cladding layer with a thickness of 700 μm on the surface of the fastener blank, and then fine-processing is performed to obtain a high-strength and high-temperature resistant alloy fastener.

[0226] The process parameters of the laser cladding treatment are as follows: the heat source for cladding is a fiber laser with a power of 4.0 kW (YLS-3000 fiber laser is used in this embodiment), the focal spot diameter of the laser beam is 2 mm, the scanning rate is 10 mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 60 g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 12 L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 15 L / min.

[0227] Comparative Example 4

[0228] This example is basically the same as Example 4, the only difference being the preparation method of the multi-element ceramic alloy cladding powder. In this example, the preparation method is:

[0229] S5-1. Preparation of gC 3 N 4 : Place urea in a muffle furnace, heat to 650°C at 8°C / min, and calcine for 4h to obtain gC 3 N 4 ;

[0230] S5-2, take 1.66g gC 3 N 4 , 0.035 mol butyl titanate, and 0.150 mol ferric acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder gC 3 N 4 -TiFeO;

[0231] S5-3, the composite oxide powder gC 3 N 4 -TiFeO was added into a tubular vacuum furnace, reacted at 1050°C for 3 h in a hydrogen atmosphere, cooled to room temperature, and ground into powder to obtain a ceramic alloy composite Ti(C,N)@Fe;

[0232] S5-4. The ceramic alloy composite and nickel powder as a base powder are mixed in a mass ratio of 3:10, and the mixture is ball-milled for 2 hours under argon protection to obtain a multi-element ceramic alloy cladding powder.

[0233] Comparative Example 5

[0234] This example is basically the same as Example 4, the only difference being the preparation method of the multi-element ceramic alloy cladding powder. In this example, the preparation method is:

[0235] S5-1. Preparation of gC 3 N 4 : Place urea in a muffle furnace, heat to 650°C at 8°C / min, and calcine for 4h to obtain gC 3 N 4 ;

[0236] S5-2, take 1.66g gC 3 N 4 , 0.035 mol butyl titanate, and 0.150 mol ferric acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder gC 3 N 4 -TiFeO;

[0237] S5-3, the composite oxide powder gC 3 N 4-TiFeO was added into a tubular vacuum furnace, reacted at 1050°C for 3 h in a hydrogen atmosphere, cooled to room temperature, and ground into powder to obtain a ceramic alloy composite Ti(C,N)@Fe;

[0238] S5-4. A Ni layer is coated on the surface of Ti(C,N)@Fe by chemical plating process to prepare multi-element ceramic alloy powder Ni@Ti(C,N)@Fe:

[0239] S5-4-1, washing the ceramic alloy composite Ti(C,N)@Fe prepared in step S5-3 with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying;

[0240] S5-4-2, adding 16 g / L SnCl 2 The solution is treated for 5-20 minutes, and then the product is taken out, washed with deionized water, and added to the multi-element plating solution. After stirring for 10 minutes, the temperature is raised to 70°C, and the pH value of the multi-element plating solution is controlled to 11 with sodium hydroxide. The plating is performed for 60 minutes. After the end, the product is allowed to stand for 5 minutes, and then filtered. The solid product is washed with deionized water, dried, and ground to obtain a multi-element ceramic alloy powder.

[0241] Among them, the amount of ceramic alloy composite Ti(C,N)@Fe added to each 1L of multi-element plating solution is 22g;

[0242] The components of the multi-element plating solution include: 35 g / L nickel sulfate, 5 g / L sodium borohydride, 15 g / L sodium citrate, 8 g / L ammonium chloride, and 15 g / L EDTA;

[0243] S5-5. Mix the multi-component ceramic alloy powder and nickel powder as a base powder in a mass ratio of 3:10, and ball-mill for 2 hours under argon protection to obtain multi-component ceramic alloy cladding powder.

[0244] Performance Testing

[0245] Test specimens of high-strength and high-temperature-resistant alloy fasteners were prepared by the methods of the embodiments and comparative examples, and the following performance tests were performed.

[0246] 1. Tensile strength and hardness test

[0247] Refer to the standard "GB / T32498-2016 Room temperature test method for tensile test of metal matrix composite materials" for room temperature tensile strength test, and refer to "GB / T 228.2-2015 Metallic material tensile test part 2: High temperature test method" for high temperature (500℃) tensile strength test;

[0248] Table 1

[0249]

[0250]

[0251] It can be seen from the test results in Table 1 that the room temperature tensile strength and high temperature tensile strength of Examples 1-5 are relatively high, which show good high temperature resistance, and within a certain range, with the increase of the Ce-Y-Nb-Mo-Fe intermediate alloy content, the tensile strength tends to gradually increase; in Comparative Example 1, no intermediate alloy is added, and the strength decreases significantly.

[0252] 2. Hardness test

[0253] (1) The surface hardness at room temperature was tested using a micro Vickers hardness tester. The test results are shown in Table 2 below:

[0254] Table 2

[0255]

[0256] (2) The surface hardness of the samples was tested by a micro Vickers hardness tester at 600°C for different holding times. The test results are as follows: Figure 3 Shown

[0257] From Table 2 and Figure 3 It can be seen from the test results that Examples 1-5 have very high surface hardness and high high temperature hardness; in Comparative Example 2, due to the lack of laser cladding treatment, the surface hardness decreases most significantly; in Comparative Example 3, although pure nickel powder is clad, the surface hardness can also be improved, but the improvement effect is limited; in Comparative Example 4, the surface hardness is significantly reduced mainly because the Ti(C,N)@Fe is not coated with the NiWCoB multi-element alloy layer. In Comparative Example 5, the Ti(C,N)@Fe is coated with Ni, and the surface hardness is reduced compared with Example 4, indicating that the NiWCoB multi-element alloy layer coating has a better effect.

[0258] 3. Wear resistance test

[0259] The MFT-5000 reciprocating friction and wear tester was used. The test conditions were: Ar gas protection atmosphere, friction load 20N, reciprocating frequency 1Hz, friction time 30min, friction stroke 15mm, and the friction pair was a corundum ball. The test was conducted at room temperature, 400℃, and 600℃ respectively. The weight before and after wear was measured using an analytical balance, and the wear amount was calculated as: weight before wear - weight after wear. The test results are shown in Table 3 and Figure 4 As shown:

[0260] Table 3

[0261]

[0262] It can be seen from the test results in Table 3 that Examples 1-5 have excellent high-temperature wear resistance, while Comparative Examples 1-5 show varying degrees of decline.

[0263] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a high-strength, high-temperature resistant alloy fastener, characterized in that: The following steps are involved: S1. Preparation of Ce-Y-Nb-Mo-Fe master alloy: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, vacuumized, and then argon gas is introduced to 0.05-0.3MPa, and smelted at 1450-1700°C for 30-90min, cooled to 650-850°C, kept warm for 5-30min, and then cooled to room temperature at a cooling rate of 10-30°C / min to obtain a Ce-Y-Nb-Mo-Fe master alloy; The composition of the Ce-Y-Nb-Mo-Fe master alloy is expressed in terms of mass percentage. include: Ce: 1.5-8.1%, Y: 0.9-5.7%, Nb: 0.45-1.26%, Mo: 4.5-18.3%, the balance is Fe and unavoidable impurity elements; S2. Weigh raw materials: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, and smelt them to obtain molten steel; S3, forging the molten steel ingot into a shape, and rough-processing to obtain a fastener blank; S4, heat treatment; S5, performing laser cladding treatment on the heat-treated fastener blank using multi-element ceramic alloy cladding powder to form a cladding layer on the surface of the fastener blank, and then fine-processing to obtain a high-strength and high-temperature resistant alloy fastener; The fastener blank comprises, by mass percentage: C: 0.27-0.42%, Si: 0.15-0.36%, Mn: 0.53-0.82%, Cr: 1.77-3.92%, Ni: 4.75-8.93%, Mo: 0.22-0.69%, V: 0.20-0.45%, Ce: 0.096-0.288%, Y: 0.066-0.198%, Nb: 0.017-0.051%, the balance is Fe and unavoidable impurity elements; The multi-element ceramic alloy cladding powder is prepared by the following method: S5-1, preparation of g-C3N4; S5-2, using g-C3N4, butyl titanate and ferric acetate as raw materials, preparing composite oxide powder g-C3N4-TiFeO by mixing and calcining; S5-3. Prepare the ceramic alloy composite Ti(C,N)@Fe by using the composite oxide powder g-C3N4-TiFeO through thermal reduction method: S5-4, coating the surface of Ti(C,N)@Fe with a NiWCoB multi-element alloy layer by chemical plating to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe; S5-5, uniformly mixing the multi-component ceramic alloy powder and the nickel powder to obtain the multi-component ceramic alloy cladding powder; The process parameters of the laser cladding treatment in step S5 are as follows: the heat source for cladding is a fiber laser with a power of 2.5-5.0kW, the focal spot diameter of the laser beam is 1.0-4.5mm, the scanning rate is 3-15mm / s, a pneumatic synchronous powder feeder is used for powder feeding, the powder feeding amount is 30-100g / min, the powder feeder uses nitrogen for powder feeding, the nitrogen gas feeding amount is 5-20L / min, and argon is used to protect the molten pool, and the argon gas feeding amount is 10-30L / min.

2. The method for preparing a high-strength, high-temperature-resistant alloy fastener according to claim 1, characterized in that: The following steps are involved: S1. preparing Ce-Y-Nb-Mo-Fe master alloy; Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, vacuumized, and then argon gas is introduced to 0.05-0.3MPa, and smelted at 1450-1700°C for 30-90min, cooled to 650-850°C, kept warm for 5-30min, and then cooled to room temperature at a cooling rate of 10-30°C / min to obtain a Ce-Y-Nb-Mo-Fe master alloy; The components of the Ce-Y-Nb-Mo-Fe master alloy include the following by mass percentage: Ce: 1.5-8.1%, Y: 0.9-5.7%, Nb: 0.45-1.26%, Mo: 4.5-18.3%, the balance is Fe and unavoidable impurity elements; S2. Weigh raw materials: C, Si, Mn, Cr, Ni, V, Fe and Ce-Y-Nb-Mo-Fe master alloy, add into electric melting furnace, smelt at 1500-1620° C. for 30-60 min, perform LF refining outside the furnace, the refining temperature is 1630-1680° C., the refining time is 5-30 min, and perform VD vacuum degassing to obtain molten steel; S3, casting the molten steel, forging the obtained ingot at 1000-1150°C, final forging at 900-950°C, air cooling to 300-350°C after forging and keeping the temperature for 4-10h to obtain a fastener blank; S4. Heat treatment: keep the fastener blank at 750-900℃ for 1-4h, cool to 500-600℃, keep for 4-10h, and then oil cool to room temperature; S5. The heat-treated fastener blank is laser clad with multi-component ceramic alloy cladding powder to form a cladding layer with a thickness of 400-800 μm on the surface of the fastener blank, and then fine-processed to obtain a high-strength and high-temperature resistant alloy fastener.

3. The method for preparing a high-strength, high-temperature-resistant alloy fastener according to claim 2, characterized in that: Step S1 is specifically as follows: Ce powder, Y powder, FeNb60 powder, Mo powder and Fe powder are added into a vacuum induction heating melting furnace, evacuated to 5 Pa, and then argon gas is introduced to 0.15 MPa, smelted at 1650°C for 45 min, cooled to 700°C, kept warm for 20 min, and then cooled to room temperature at a cooling rate of 20°C / min to obtain a Ce-Y-Nb-Mo-Fe intermediate alloy.

4. The method for preparing a high-strength and high-temperature resistant alloy fastener according to claim 3, characterized in that: The components of the Ce-Y-Nb-Mo-Fe master alloy include the following by mass percentage: Ce: 4.8%, Y: 3.3%, Nb: 0.85%, Mo: 11.4%, the balance is Fe and inevitable impurity elements; During the smelting process of step S2, the addition amount of the Ce-Y-Nb-Mo-Fe master alloy is 2-6% of the total raw material mass.

5. The method for preparing a high-strength and high-temperature resistant alloy fastener according to claim 4, characterized in that: The fastener blank comprises, by mass percentage: C: 0.36%, Si: 0.21%, Mn: 0.65%, Cr: 2.33%, Ni: 6.52%, V: 0.35%, Mo: 0.57%, Ce: 0.24%, Y: 0.165%, Nb: 0.0425%, and the remainder is Fe and inevitable impurity elements.

6. The method for preparing a high-strength and high-temperature resistant alloy fastener according to claim 1, characterized in that: The multi-element ceramic alloy cladding powder is prepared by the following method: S5-1, placing urea in a muffle furnace, heating to 580-700°C at 5-10°C / min, and calcining for 2-6h to obtain g-C3N4; S5-2, 1.25-3.23 g g-C3N4, 0.0155-0.07 mol butyl titanate, and 0.113-0.45 mol ferric acetate were mixed and ground for 45-90 min, and the obtained mixture was calcined at 550-680 ° C for 1-4 h, cooled to room temperature, and the product was ground to obtain a composite oxide powder g-C3N4-TiFeO; S5-3, adding composite oxide powder g-C3N4-TiFeO into a tubular vacuum furnace, reacting at 920-1100°C for 1-5h in a hydrogen atmosphere, cooling to room temperature, grinding to obtain a ceramic alloy composite Ti(C,N)@Fe; S5-4. A NiWCoB multi-element alloy layer is coated on the surface of Ti(C,N)@Fe by chemical plating process to prepare multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe: S5-4-1, washing the ceramic alloy composite Ti(C,N)@Fe prepared in step S5-3 with a hydrochloric acid solution having a mass fraction of 2-10%, then washing with deionized water until neutral, then washing with ethanol, and drying; S5-4-2, adding the ceramic alloy composite Ti(C,N)@Fe pretreated in step S5-4-1 to a 7-23 g / L SnCl2 solution for 5-20 min, taking it out, washing it with deionized water, adding it to a multi-element plating solution, stirring it for 4-15 min, heating it to 65-77°C, controlling the pH value of the multi-element plating solution to 10-11, plating it for 30-90 min, letting it stand for 2-10 min after completion, filtering it, washing the solid product with deionized water, drying it, and grinding it to obtain a multi-element ceramic alloy powder NiWCoB@Ti(C,N)@Fe; The amount of ceramic alloy composite Ti(C,N)@Fe added to each 1L of multi-element plating solution is 8-30g; The components of the multi-element plating solution include: 22-40 g / L nickel sulfate, 3-18 g / L sodium tungstate, 5-20 g / L cobalt sulfate, 1-5 g / L sodium tetraborate, 2-10 g / L sodium borohydride, 5-25 g / L sodium citrate, 5-20 g / L ammonium chloride, and 10-30 g / L EDTA; S5-5. Mix the multi-component ceramic alloy powder and nickel powder in a mass ratio of 0.5-4.5:10, and ball-mill for 1-5 hours under argon protection to obtain multi-component ceramic alloy cladding powder.

7. A high-strength, high-temperature-resistant alloy fastener, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for processing high-strength fastener and hot-treating process

    CN102260830B

  • Preparation method of high-performance fastener and fastener

    CN116770038A

  • Ejector head for rolling high-alloy steel pipe and manufacturing method thereof

    CN117358757A